Polyhydroxy amide stabilizer for synergistic zirconium carbonate water repellent agent, water repellent agent composition and preparation method

By combining a polyhydroxyamide stabilizer with a zirconium carbonate water-resistant agent, the gelation and precipitation problems of the zirconium carbonate water-resistant agent during storage were solved, thereby improving the wet friction resistance and storage stability of the coated paper.

CN120967723APending Publication Date: 2025-11-18ZHEJIANG TRANSFAR WHYYON CHEM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510970036.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing zirconium carbonate water-resistant agents are prone to forming hydrogels or white precipitates during storage, affecting storage and use performance. Conventional stabilizers are not effective under high temperature or high humidity conditions.

Method used

A synergistic zirconium carbonate water-resistant agent was prepared by using a polyhydroxy amide stabilizer through salt formation and ring-opening amidation reactions. The addition ratio was 0.1% to 3.0% wt. The agent contained polyhydroxy monocarboxylic acid or its lactone and polyethylene polyamine. It was used in the zirconium carbonate water-resistant agent to enhance the chelating ability of zirconium and improve stability.

Benefits of technology

Adding polyhydroxyamide stabilizers to the coating of coated paper improves the stability of the water-resistant agent under cold and hot storage conditions, while maintaining its activity and enhancing the wet friction resistance of the coated paper.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120967723A_ABST
    Figure CN120967723A_ABST
Patent Text Reader

Abstract

The invention discloses a polyhydroxy amide stabilizer of a synergistic zirconium carbonate water-resistant agent, a water-resistant agent composition and a preparation method, the polyhydroxy amide stabilizer comprises polyhydroxy amide with 1-2 amides, 1-3 secondary amino groups and 4-12 hydroxyl groups and water, and the solid content of the polyhydroxy amide stabilizer is 10-90% wt. The synergistic stabilizing agent has the advantages that the synergistic stabilizing agent has a proper zirconium chelating capability, so that the synergistic stabilizing agent can prevent mutual combination of zirconium to a certain extent to improve the storage stability of the water repellent agent, and the activity of the water repellent agent cannot be reduced due to too strong zirconium chelating capability. When the stabilizer is added into a coating water-resistant agent, the cold storage and heat storage stability and the application effect are improved along with the increase of the addition amount within a certain range, and the improvement is better than that of other conventional micromolecular stabilizers such as polyol, alcohol acid, alcohol amine and urea.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of papermaking additives technology, specifically to a polyhydroxyamide stabilizer for enhancing zirconium carbonate water-resistant agents, a water-resistant agent composition, and a preparation method thereof. Background Technology

[0002] During the printing process, coated paper requires a coating with good dry rubbing strength, wet rubbing resistance (wet rubbing strength), and printability. Wet rubbing resistance is primarily improved by adding water-repellent agents to the coating. Water-repellent agents include various types such as amino resins, polyamide-polyamine-epoxychloropropane resins, ethylene glycol-modified resins, polyurea-polyamide resins, and zirconium carbonate salts. Among these, zirconium carbonate salts have become one of the most mainstream water-repellent agents due to their rapid curing speed, formaldehyde-free nature, strong coordination reaction ability, wide applicable pH range, and good coating color, making them particularly popular with high-end coated paper users.

[0003] However, due to the strong coordination ability of zirconium, it can not only coordinate and combine with polar functional groups such as amino, hydroxyl, and carboxyl groups in coating components, but zirconium ions can also cross-link with each other through double hydroxyl bridges to form hydrogels or be encapsulated by carbonate groups to form white precipitates, affecting the storage and use of the product.

[0004] Many researchers have improved the storage stability of zirconium carbonate water-resistant agents by adding stabilizers. Patent US4061720A improves the stability of zirconium carbonate by adding 1-2% tartaric acid or gluconic acid by mass, which to some extent prevents the interaction between zirconium atoms. However, tartaric acid and gluconic acid have excessively strong chelating power for zirconium; excessive addition can easily lead to reduced coordination ability, decreased reactivity, and poor application performance. Patent CN102776803A uses glycerol as a stabilizer for zirconium carbonate in addition to tartaric acid. However, the coordination ability between glycerol and zirconium is insufficient, requiring a large amount to improve the room temperature storage stability of the zirconium carbonate water-resistant agent. Moreover, turbidity and precipitation still occur under storage conditions of 4℃ or 50℃. Patent CN109250754A, in addition to tartaric acid and glycerol, also uses citric acid, polyethylene glycol, and urea as stabilizers. Citric acid, similar to tartaric acid, has an excessively strong ability to chelate zirconium, improving storage stability but easily leading to a decrease in application performance. Polyethylene glycol and urea, similar to glycerol, have insufficient binding ability with zirconium, improving stability at 4°C, but still exhibiting turbidity and precipitation under 50°C heat storage conditions. Patent JP2013075813A, besides the aforementioned polyols, alkyds (and their salts), also uses ethanolamines such as triethanolamine as stabilizers, and studies the optimal ratio of triethanolamine to acetate-modified polyvinyl alcohol using crosslinking strength as the criterion. However, this result is inconsistent with the application effect test results on coated paper. Under the stronger alkalinity and more complex composition environment of the coating, increasing the amount of triethanolamine added did not significantly improve the wet rubbing strength of the coated paper. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to provide a polyhydroxyamide stabilizer, a water-resistant agent composition, and a preparation method for a synergistic zirconium carbonate water-resistant agent that has appropriate zirconium chelating ability, which can both prevent the mutual bonding between zirconium to a certain extent to improve the storage stability of the water-resistant agent, and prevent the water-resistant agent activity from being reduced due to excessive zirconium chelating ability.

[0006] To achieve the above effects, the present invention provides a polyhydroxyamide stabilizer for enhancing zirconium carbonate water-resistant agents, comprising a polyhydroxyamide having 1 to 2 amides, 1 to 3 secondary amines, 4 to 12 hydroxyl groups and water, wherein the solid content of the polyhydroxyamide stabilizer is 10-90% wt.

[0007] In one embodiment of the present invention, the product is obtained by salting or ring-opening amidation of a polyhydroxy monocarboxylic acid or its lactone and a polyethylene polyamine under nitrogen protection and high temperature, followed by dilution with hot water. The product is then added to a zirconium carbonate water-resistant agent in a certain proportion to take effect. The molar ratio of the polyhydroxy monocarboxylic acid or its lactone to the polyethylene polyamine is 1.1:1.0 to 1.9:1.0.

[0008] In one embodiment of the present invention, the polyethylene polyamine is selected from one or more of diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

[0009] In one embodiment of the present invention, the polyhydroxy monocarboxylic acid or its lactone is selected from one or more of D-xyloic acid and its salts, D-xyloic acid lactone, D-gluconic acid and its salts, D-iduronic acid and its salts, D-gulonic acid and its salts, D-gluconic acid-1,4-lactone, D-gluconic acid-δ-lactone, D-glucoheponic acid and its salts, and D-glucoheponic acid lactone.

[0010] In one embodiment of the present invention, the salt-forming amidation reaction temperature is 140–180°C, and the ring-opening amidation reaction temperature is 60–120°C.

[0011] The present invention also provides a water-resistant agent mixture comprising a zirconium carbonate water-resistant agent and a polyhydroxyamide stabilizer that enhances the zirconium carbonate water-resistant agent as described in any one of the present invention.

[0012] In one embodiment of the present invention, the addition ratio, based on the solid content of the polyhydroxyamide stabilizer that enhances the zirconium carbonate water-resistant agent, is 0.1% to 3.0% wt of the solid content of the zirconium carbonate water-resistant agent.

[0013] In one embodiment of the present invention, the water-resistant agent mixture includes one or more of sodium zirconium carbonate, potassium zirconium carbonate, ammonium zirconium carbonate, and zinc zirconium carbonate.

[0014] The present invention also provides a method for preparing a mixture of water-resistant agents, comprising adding a polyhydroxyamide stabilizer to the zirconium carbonate water-resistant agent before the synthesis of the zirconium carbonate water-resistant agent.

[0015] In one embodiment of the present invention, a polyhydroxyamide stabilizer for enhancing the zirconium carbonate water-resistant agent is added after the synthesis of the zirconium carbonate water-resistant agent.

[0016] The advantages of this invention are: the synergistic stabilizer has an appropriate ability to chelate zirconium, which can both prevent the mutual bonding between zirconium molecules to a certain extent to improve the storage stability of the water-resistant agent, and prevent the water-resistant agent's activity from decreasing due to excessive zirconium chelation ability. When added to the coating water-resistant agent, within a certain range, the cold storage and hot storage stability and application effect are improved with the increase of the amount added, and the improvement is better than that of other conventional small molecule stabilizers such as polyols, alkyds, alkanolamines and ureas.

[0017] Instruction manual illustrations

[0018] Figure 1 The chemical structural formula of the polyhydroxyamide of this invention is shown below.

[0019] In the diagram, n = 3–5, m = 2–4, and R = H or another polyol monoacyl group. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0022] Example 1

[0023] In a 500 mL four-necked glass flask equipped with heating, nitrogen protection, stirring, tail gas collection, and a thermometer, 270.0 g of D-gluconic acid-δ-lactone was added. After nitrogen purging, 105.0 g of diethylenetriamine was pumped in using a peristaltic pump, with a molar ratio of 1.49:1. The mixture was heated to 80 °C and held at 80 ± 5 °C for 6 hours to carry out a ring-opening amidation reaction, resulting in a paste-like molten state. After the holding period, hot water at 80 °C was added to dilute the mixture to a 50% concentration, and the mixture was stirred until homogeneous to obtain synergistic stabilizer-1.

[0024] Add the synergistic stabilizer-1 to a commercially available potassium zirconium carbonate-1 (solid content 31.5%, zirconium oxide content 7.3%, no stabilizer added), which is 2.0% of the solid mass of the water-resistant agent, and stir well.

[0025] Example 2

[0026] Except for adjusting the addition ratio of synergist-stabilizer-1 to 0.5%, everything else is the same as in Example 1.

[0027] Example 3

[0028] Except for adjusting the addition ratio of synergist-stabilizer-1 to 1.0%, everything else is the same as in Example 1.

[0029] Example 4

[0030] Except for adjusting D-glucono-δ-lactone to 210.2g (molar ratio of 1.16:1) to obtain synergistic stabilizer-2, everything else was the same as in Example 1.

[0031] Example 5

[0032] Except for adjusting D-glucono-δ-lactone to 320.5g (molar ratio of 1.77:1) to obtain synergistic stabilizer-3, everything else was the same as in Example 1.

[0033] Example 6

[0034] Except for adjusting diethylenetriamine to 150.0g triethylenetetramine (molar ratio of 1.48:1) to obtain synergistic stabilizer-4, everything else was the same as in Example 1.

[0035] Example 7

[0036] Except for adjusting diethylenetriamine to 190.0g triethylenetetramine (molar ratio of 1.51:1) to obtain synergistic stabilizer-5, everything else was the same as in Example 1.

[0037] Example 8

[0038] Except for adjusting D-glucono-δ-lactone to 322.4g D-glucono-δ-lactone (molar ratio of 1.52:1) to obtain synergistic stabilizer-6, everything else was the same as in Example 1.

[0039] Example 9

[0040] In a 500 mL four-necked glass flask equipped with heating, nitrogen protection, stirring, tail gas collection, and a thermometer, 300.2 g of D-gluconic acid (50% solution) was added. After nitrogen purging, 49.8 g of diethylenetriamine was pumped in using a peristaltic pump, with a molar ratio of 1.59. The mixture was heated to 90 °C and held at 90 ± 5 °C for 4 hours until it reached a paste-like molten state. The temperature was then raised to 170 °C and held at 170 ± 5 °C for another 2 hours to carry out the salt-forming amidation reaction. After the holding time was completed, hot water at 80 °C was added to dilute the solution to 50% concentration, and the mixture was stirred until homogeneous to obtain synergistic stabilizer-7.

[0041] Add synergistic stabilizer-7 to commercially available potassium zirconium carbonate-1, which is 2.0% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0042] Example 10

[0043] Add the enhanced stabilizer-1 to a commercially available zirconium ammonium carbonate-1 (solid content 32.1%, zirconium oxide content 7.2%, no stabilizer added), which is 0.5% of the solid mass of the water-resistant agent, and stir evenly.

[0044] Example 11

[0045] Add the synergistic stabilizer-1 to commercially available zirconium ammonium carbonate-1, which is 1.0% of the solid content of the water-resistant agent, and stir until homogeneous.

[0046] Example 12

[0047] Add the synergistic stabilizer-1 to commercially available zirconium ammonium carbonate-1, which is 2.0% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0048] Comparative Example 1

[0049] Commercially available potassium zirconium carbonate (ZrCO-1) contains no added stabilizers.

[0050] Comparative Example 2

[0051] Add tartaric acid to commercially available potassium zirconium carbonate-1 at 0.5% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0052] Comparative Example 3

[0053] Add tartaric acid to commercially available potassium zirconium carbonate-1 at 1.0% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0054] Comparative Example 4

[0055] Add tartaric acid to commercially available potassium zirconium carbonate-1 at 2.0% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0056] Comparative Example 5

[0057] Add tartaric acid to commercially available potassium zirconium carbonate-1 at 5.0% of the solid mass of the water-resistant agent, and stir until homogeneous.

[0058] Comparative Example 6

[0059] Add 5.0% of commercially available potassium zirconium carbonate-1 (based on solids) to synergist-stabilizer-1 and stir until homogeneous.

[0060] Comparative Example 7

[0061] Add 2.0% of commercially available potassium zirconium carbonate (calculated as solids) to glycerol and stir until homogeneous.

[0062] Comparative Example 8

[0063] Add 2.0% of commercially available potassium zirconium carbonate (based on solids) to gluconic acid (50% solution) and stir until homogeneous.

[0064] Comparative Example 9

[0065] Commercially available zirconium carbonate-1 contains no added stabilizers.

[0066] Comparative Example 10

[0067] According to the alcohol-amine ratio in Example 1, it was directly added to commercially available potassium zirconium carbonate-1, and the total amount added was 2.0% of the solid mass of the water-resistant agent.

[0068] Test methods and results

[0069] 1. Wet Friction Resistance Test Method

[0070] A coating material from a coated paper manufacturer before the addition of a water-resistant agent was used as the base material. Water-resistant agents were added at mass ratios (based on calcium carbonate weight) of 0.2%, 0.4%, and 0.6% respectively under high-speed dispersion conditions and stirred thoroughly. Coated base paper from the same manufacturer, after coating, roller drying, calendering, and constant temperature and humidity treatment, was used to take paper samples, which were fixed on a wet friction tester. A measured amount of water was added, and a friction test was conducted. The water was collected, and its turbidity was measured. The lower the turbidity, the lower the proportion of coating material removed after the friction test, and the better the wet friction resistance. The wet friction test results are given as the average turbidity of three parallel tests.

[0071] Table 1 Results of wet friction test

[0072]

[0073] The technical solution presented in this application significantly improves the wet rubbing resistance of the paper compared to the solution without added synergistic stabilizers, even at different amounts of water-resistant agent. The improvement is greater than that achieved with other small-molecule stabilizers. A 0.6% addition increases the wet nap strength by 40%.

[0074] 2. Storage stability test

[0075] 50g samples were placed in a 4℃ refrigerator, a 25℃ constant temperature box, and a 50℃ oven for 2 weeks respectively to observe storage stability, including whether gelation, turbidity, precipitation, or increased viscosity occurred.

[0076] Table 2 Storage stability test results

[0077] refrigeration Store at room temperature thermal storage Example 1 Stablize Stablize Stablize Example 2 Stablize Stablize Stablize Example 3 Stablize Stablize Stablize Example 4 Stablize Stablize Stablize Example 5 Stablize Stablize Stablize Example 6 Stablize Stablize Stablize Example 7 Stablize Stablize Stablize Example 8 Stablize Stablize Stablize Example 9 Stablize Stablize Stablize Example 10 Stablize Stablize Stablize Example 11 Stablize Stablize Stablize Example 12 Stablize Stablize Stablize Comparative Example 1 Slightly cloudy with white sediment at the bottom. Stablize gel Comparative Example 2 Slightly cloudy with white sediment at the bottom. Stablize Increased viscosity Comparative Example 3 Slightly cloudy with white sediment at the bottom. Stablize Stablize Comparative Example 4 Stablize Stablize Stablize Comparative Example 5 Stablize Stablize Stablize Comparative Example 6 Stablize Stablize Stablize Comparative Example 7 Cloudy with white sediment at the bottom Stablize Cloudy with white sediment at the bottom Comparative Example 8 Stablize Stablize Stablize Comparative Example 9 Stablize Stablize gel Comparative Example 10 Slightly cloudy with white sediment at the bottom. Stablize Stablize

[0078] The water-resistant agent compositions obtained by the technical solution of this application all exhibit good stability.

Claims

1. A polyhydroxyamide stabilizer for synergistic zirconium carbonate salt-based water repellents, characterized by, The polyhydroxyamide stabilizer comprises a polyhydroxyamide having 1-2 amides, 1-3 secondary amine groups, and 4-12 hydroxyl groups, and water, and the solid content of the polyhydroxyamide stabilizer is 10-90%wt.

2. The method of producing a multi-hydroxy amide stabilizer for a synergistic zirconium carbonate-based water repellent agent according to claim 1, characterized by, The polyhydroxyamide stabilizer comprises a polyhydroxyamide obtained by salifying amide reaction or ring-opening amide reaction of a polyhydroxy monocarboxylic acid or lactone thereof and a polyethylene polyamine under nitrogen protection and high temperature, and then diluting with water, and the molar ratio of the polyhydroxy monocarboxylic acid or lactone thereof to the polyethylene polyamine is 1.1:1.0-1.9:1.

0.

3. The synergistic zirconium carbonate salt-based water repellent polyhydroxyamide stabilizer of claim 1, wherein, The polyethylene polyamine is selected from one or more of diethylene triamine, triethylene tetramine, and tetraethylene pentamine.

4. The synergistic zirconium carbonate salt-based water repellent polyhydroxyamide stabilizer of claim 1, wherein, The polyhydroxy monocarboxylic acid or lactone thereof is selected from one or more of D-xylose acid and salts thereof, D-xylose lactone, D-gluconic acid and salts thereof, D-idonic acid and salts thereof, D-gulonic acid and salts thereof, D-glucono-1,4-lactone, D-glucono-δ-lactone, D-glucoheptonic acid and salts thereof, and D-glucoheptonic lactone.

5. The synergistic zirconium carbonate salt-based water repellent polyhydroxyamide stabilizer of claim 1, wherein, The salifying amide reaction temperature is 140-180°C, and the ring-opening amide reaction temperature is 60-120°C.

6. An anti-water agent mixture characterized in that, The polyhydroxyamide stabilizer comprises a zirconium carbonate water-resistant agent and the synergistic polyhydroxyamide stabilizer of any one of claims 1-5.

7. The water repellent agent mixture according to claim 1, wherein The addition ratio is 0.1%-3.0%wt of the solid content of the zirconium carbonate water-resistant agent.

8. The water repellent agent mixture according to claim 1, wherein The zirconium carbonate water-resistant agent comprises one or more of sodium zirconium carbonate, potassium zirconium carbonate, ammonium zirconium carbonate, and zinc zirconium carbonate.

9. The method of claim 6-8, wherein the water repellent mixture is prepared by, The polyhydroxyamide stabilizer comprises the synergistic polyhydroxyamide stabilizer added before synthesis of the zirconium carbonate water-resistant agent.

10. The method of claim 6-8, wherein the water repellent mixture is prepared by, The polyhydroxyamide stabilizer comprises the synergistic polyhydroxyamide stabilizer added after synthesis of the zirconium carbonate water-resistant agent.

Citation Information

Patent Citations

  • Preparation method for preparing potassium-zirconium-carbonate water repellent agent

    CN102776803A

  • Preparation method and application of zirconium carbonate salt

    CN109250754A

  • Ammonium zirconium carbonate aqueous solution

    JP2013075813A

  • Preparation of ammonium and potassium zirconium carbonates

    US4061720A